Typical case: herpes zoster - Baldivia,Guilherme Cristianini (2015)
Summary The varicella zoster virus is the causative agent of herpes zoster and varicella. In herpes zoster, the virus dormant within dorsal root ganglia is reactivated, resulting in painful vesicular lesions overlying an erythematous base.